On the influence of axial cylinder distortions on lubricant film and friction force of top piston ring conjunction near to TDC. (2nd October 2022) - Nikolakopoulos, Pantelis G.; Antonakakis, Giorgos; Zavos, Anastasios
ABSTRACT: The purpose of this paper was to understand how axial cylinder distortions influence the tribological performance of piston ring. The current model contains the effects of axial distortions and ring conformability under mixed to hydrodynamic regimes of lubrication through computational fluid dynamics predictions. The axial cylinder profiles were modelled using series of sinusoidal waves. The effect of axial distortions on ring wear rate was determined using the Archard's model. The ring friction and minimum lubricant film were predicted for low and high combustion pressures near to top dead centre. The study shows that, when the maximum combustion pressure rises, the different wear identities affect the operation of the ring friction much more limited, while the number of sine waves are more pronounced. Finally, it is proved that, even the increase of oil film thickness, it does not presuppose the reduction of friction when it comes to shaping the surface of the cylinder liner. GRAPHICAL ABSTRACT: UF0001